FUNGSI DAN GAYA KEPEMIMPINAN KEPALA DESA PEREMPUAN DI DESA MASARAN, BANYUATES SAMPANG - Holilah, Holilah (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article aims to explore the function and style of women’s leadership. It deals with a case study of Head of Masaran Village, Banyuates, Sampang. In this research the writer employs qualitative approach and has formulated two main questions, are: first, how is the function of women’s leadership as the village head?; second, how is the leadership style of thiswoman as thevillage head? The research results in two conclusions, are; first, the woman’s leadership does not function effecttively as she deals merely with administrative aspects, while the top-management functions are performed mostly by her husband. This matter cannot, however, be separated from gender bias, patriarchal culture, and the lack of ability of the village head. Second,the woman’s leadership style can be categorized as laissez fairestyle. This is because as a leaderthe woman does not fully participate in the implementation of village’s agenda and activities for any responsiblity is handled by her husband.